IMPLIKASI GLOBALISASI DALAM POLA KEKERASAN SEKTARIANISME DI INDONESIA - Wibisono, Bintang Indra; Pasopati, Rommel Utungga (Masyarakat Indonesia, 2018)
The last decade was marked by sectarian violence in Indonesia. In 2008, violence occurred on Ahmadiyah groups in Cikeusik, Pandeglang and in Manis Lor, Kuningan in 2010. Violence also experienced by Shia groups in Bangil and Sampang in 2011 and 2012. Some of these events indicate the interaction between globalization and identity that is not always peaceful because it affirms identity by exclusion until applying violence to another in the process. There is a landmark that the rampant exclusion to violence is facilitated by globalization. This study looks at this link by analyzing how globalization allows for patterns of violence in sectarianism in Indonesia. Globalization forms the basis of this study primarily as a condition that facilitates the flow of information and communication. As a result, individuals become more open to the possibilities or find the fundamentally inclined side. The authors argue that globalization also enables an increase in the spread of violence against other rather than bringing tolerance and togetherness. This can be seen from the hate narratives formed against Ahmadiyya and Shiite groups by conservative groups. In conclusion, globalization tends to serve as enabling conditions rather than actors who form discourse. Against the pattern of sectarian violence, globalization also allows the narrative of hatred to spread into violence as normal in strengthening identity. In other words, far from acknowledging the truth, globalization in fact also enables subscribers to the pattern of sectarian violence in Indonesia.